Regioisomeric characterization of triacylglycerols using silver-ion HPLC/MS and randomization synthesis of standards - Lísa, Miroslav; Velínská, Hana; Holcapek, Michal (Analytical chemistry, 2009)
Silver-ion normal-phase high-performance liquid chromatography (HPLC) provides a superior separation selectivity for lipids differing in the number and position of double bonds in fatty acid chains including the resolution of triacylglycerol (TG) regioisomers under optimized conditions. Our silver-ion HPLC method is based on the coupling of three columns in the total length of 75 cm and a new mobile phase gradient consisting of hexane-acetonitrile-2-propanol which provides better resolution and also reproducibility in comparison to previously used mobile phases. In our work, the chemical interesterification (randomization) of single-acid TG standards is used for the generation of regioisomeric series of TGs, because it provides a random distribution of fatty acids in TGs at well-defined concentration ratios. The baseline separation of regioisomeric TG pairs containing up to three double bonds and the partial separation of TG regioisomers with four to seven double bonds are reported for the first time. Our silver-ion high-performance liquid chromatography/mass spectrometry (HPLC/MS) method is applied for the regioisomeric characterization of complex samples of plant oils and animal fat, where the results clearly demonstrate different preference of sn-2 occupation in plants (mainly unsaturated fatty acids) versus animal fat (mainly saturated fatty acids).
Keywords: Animals; mastné kyseliny; Reference Standards; Fatty Acids; triglyceridy; Silver; Reproducibility of Results; vysokoúčinná kapalinová chromatografie; Triglycerides; Plant Oils; Stereoisomerism; stereoizomerie; Fatty Acids, Unsaturated; hmotnostní spektrometrie; reprodukovatelnost výsledků; Chromatography, High Pressure Liquid; referenční standardy; nenasycené mastné kyseliny; oleje rostlin; Mass Spectrometry; zvířata; stříbro